Pengembangan sistem komposting melalui Bank Sampah di Desa Petani, Kecamatan Bathin Solapan - Suwondo Suwondo; Darmadi Darmadi; Andri Hendrizal (Unri Conference Series: Community Engagement, 2020)
Community service is an effort to disseminate science, technology and art to society. These activities must be able to provide an added value for the community, both in economic activities, policies, and changes in (social) behavior. The goal of community service activities in Farmers Village, Bathin Solapan District is that the community can play an active role in optimizing existing waste banks in order to form a good waste management system, improving the clean culture and economy of the community. The community can take advantage of the organic waste collected from each resident's house which is submitted directly to the waste bank for the composting process. The level of achievement of the program targets carried out in the farmer village of the Inner Solapan sub-district is very good and right on target, this is based on the enthusiasm of the community and the spiritual (adat) chairman in seeing the training process for processing organic waste into compost using a composter drum that has been prepared by the service team riau university and riau university students. Drum composter is an effective compost processing method for the community in Desa Petani, Kecamatan Bathin Solapan, on a household scale. Analysis of the development of a composting system through a waste bank in a farmer village, in the sub-district of Inner Solapan aims for the community to play an active role in optimizing existing waste banks to form a good waste management system.